Depression, anxiety and anger symptoms among children in different kinds of custodies - Soffía Dóra Sigurðardóttir 1970- (2017)
Divorce rate has increased in the past years. It is also more common that children live with both parents in shared physical custody instead of single parent’s households. The aim of this study is to examine whether different forms of custodies impact adolescent’s mental health in the forms of depressed mood, anxiety and anger. To estimate those symptoms in different kind of custodies, data from the National Survey of Icelandic Adolescents, Youth in Iceland 2016 were used. The study is population based with 10.687 adolescents in 8th, 9th and 10th grade of elementary school taking part. The independent variables were three and reflected the form of residence, intact family, single parent household and shared physical custody. The dependent variables were also three; depressed mood, anxiety and anger. The results reveal that children living with both parents as intact family measure lower in depressed mood, anxiety and anger, than children living in other kind of families. The regression weights for intact family vs. single parent ranged from 0.12 to 0.15 while the regression weights for intact family vs. shared physical custody ranged from 0.03 to 0.04. Therefore, those who live in shared physical custody are better off than those who live in single parent’s households and are closer to how it is within intact families. Keywords: depressed mood, anxiety, anger, intact family, single parent households, shared physical custody